Towards an assessment of the disciplinary skills of the degree courses L-19. The process of test construction - Francesca Bracci; Alessandra Romano (Firenze University Press, 2018)
The article presents the first step of the research process undertaken to construct a test - composed of batteries of closed ended questions - for the assessment of the disciplinary skills of students of degree courses in Education and Training Sciences (L-19) of Italian universities that joined the Teco-D project developed by Anvur. It describes the qualitative phase conducted to define the set of items to be submitted to the statistical validation procedure, and which, after the adjustments and calibrations deemed necessary on the basis of the results of the analysis to be carried out, will constitute the test for the assessment of the disciplinary skills provided as part of the Teco-D project.   Verso una valutazione delle competenze disciplinari dei Corsi di Laurea L-19. La costruzione di un test Il contributo presenta il primo step del processo di ricerca intrapreso per costruire un test - composto di batterie di domande a risposta chiusa - di valutazione delle competenze disciplinari di studenti e studentesse di corsi di laurea in scienze dell'educazione e della formazione (L-19) di università italiane che hanno aderito al progetto Teco-D sviluppato da Anvur. È descritta la fase qualitativa condotta per definire l'insieme di item da sottoporre a procedura di validazione statistica e che, dopo gli aggiustamenti e le calibrazioni ritenuti necessari sulla base dei risultati delle analisi che saranno effettuate, costituirà il test di valutazione delle competenze disciplinari previsto nell'ambito del progetto Teco-D.